Kinetic Study of Co-pyrolysis of Kelakai (Stenochlaena palustris) and Low-rank Coal (Lignite) - Fadhillah, Hilda Nur; Wijayanti, Hesti; Mardina, Primata; Juwita, Rinna; Nata, Iryanti Fatyasari; Putra, Meilana Dharma; Madani, Zikri Daffa Aulia; Hendrawan, Rangga Dwi (Politeknik Negeri Malang, 2025)
Recently, fossil fuels have still become a main source of energy and chemicals. Biomass conversion has become a promising technology to convert biomass into bio-energy and bio-chemicals. Kelakai, as a potential biomass, is abundant in wetland areas such as Kalimantan (Indonesia) and many other Asian regions, so that low-rank coal (lignite). Co-pyrolysis, the combined pyrolysis of biomass and lignite, is an attractive technique considering to its potential to enhance the efficiency of pyrolysis products. In this study, the thermal decomposition behavior and kinetic of co-pyrolysis of kelakai and lignite at various mass ratio composition (1:0, 3:1, 1:1, 1:3, and 0:1) were investigated. The experiments were performed on a thermogravimetric analyzer (TGA). The TGA result indicated that the kelakai highly decomposed at 257-400℃, while lignite was 286-500℃. Their blends were in between. In addition, thermogravimetric data were subsequently applied to a kinetic analysis based on the Arrhenius equation, with a first-order reaction. The kinetic analysis results, including activation energy and pre-exponential factor, were determined for the kelakai and lignite mixture were found to be in the range of 10.22-10.98 kJ/mol and 0.0651-0.1351 min-1, respectively. Knowledge of thermal decomposition characteristics of kelakai and its kinetics is essential for optimizing pyrolysis design. The co-pyrolysis kelakai and lignite resulted in the highest bio-oil yield of 26.86 wt% at the ratio of 0:1 and the lowest yield of 12.51 wt% for the ratio of 1:0, when using mixed ratios of kelakai and lignite, the highest yield was 24.60% (1:3) and the lowest yield was 21.18 wt% (1:1).